INFLUENCE CASH TURNOVER TOGROSS PROFIT MARGIN IN PULP AND PAPER SUB SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE 2018-2021 PERIOD - Mai Della Safrina; Nelva Siskawati (Indragiri Research Center (ingreat), 2023)
This research aims to test the effect of cash turnover to gross profit margin in pulp and paper sub-sector companies listed on the Indonesian stock exchange. This research sample uses the method purposive sampling as many as 8 pulp and paper sub-sector companies with a term of 4 years. This research data analysis is quantitative analysis, as a calculation tool using SPSS analysis. The resulting value of the coefficient of determination (R2) of 0.115 indicates that the variable cash turnover of the company is influenced by gross profit margin amounting to 11.5% and the remaining 88.5% is influenced by other variables. Variable test results gross profit margin partially shows that the variable cash turnover has a calculated t of -1.974. Based on the results of table calculations in the t test, a significance value of 0.058 was obtained. Thus, it can be compared that the significance value is 0.058 > 0.05, so HOaccepted and Ha rejected this shows thatcash turnover does not have a significant effect on gross profit margin in pulp and paper sub-sector companies. Based on the research results, it shows that the manager's cash turnover is less effective because uncollected receivables make cash receipts take a long time to receive. Apart from that, the company must be able to maximize its cash to increase sales and also reduce receivables gross profit margin produced can increase.